2022
DOI: 10.29173/isotl609
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Power and Privilege of Failure in Higher Education

Abstract: Learning from failure is a core component to education, however it is not often deliberately taught in university courses. In addition, while the rhetoric around taking risks, embracing failure, and bouncing back is pervasive in higher education, the corresponding structural supports are lacking. The purpose of the current work is to explore ways we can visualize and illustrate the power and privilege involved with embracing and learning from failure in the context of higher education. We offer three approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The critical next step is to turn these suggestions into tangible changes in the culture of university classrooms. Although some faculty may feel resistant to implementing such changes (Ross et al 2023), one must consider that there is no expectation to implement all of these suggestions at once. Instructors can challenge their discomfort and begin with small steps in implementing one or a few suggestions they feel are within their capacity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The critical next step is to turn these suggestions into tangible changes in the culture of university classrooms. Although some faculty may feel resistant to implementing such changes (Ross et al 2023), one must consider that there is no expectation to implement all of these suggestions at once. Instructors can challenge their discomfort and begin with small steps in implementing one or a few suggestions they feel are within their capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In interviews with university faculty, Ross et al (2023) identified a hesitancy to incorporate failure-based interventions in the classroom, specifically in the provision of opportunities for failure and desirable difficulties. This suggests a disconnect between the known pedagogical value of failure and institutional expectations and policies.…”
Section: Implications For Institutionsmentioning
confidence: 99%
See 1 more Smart Citation